World statistics on mining and utilities... [200 -]- (UNIDO ViennaAT)
Presents data from selected industrialised countries in the Commonwealth of Independent Countries (CIS), Europe, East Asia, Canada, USA, Australia, Israel, New Zealand and South Africa.
Documentation Centre has: 2012; 2014; 2018